Efficacy and safety of low-intensity ultrasound therapy for myofascial pain syndrome: a systematic review and meta-analysis - Xize Li; Yijun Lin; Peijue He; Qian Wang (BMC Musculoskeletal Disorders)
Abstract Background Myofascial Pain Syndrome (MPS) is a common pain disorder characterized by the presence of trigger points within the muscles or fascia. Low-intensity ultrasound therapy, as a noninvasive modality, has indeed found application in the management of MPS, but its efficacy for myofascial pain syndrome has still been controversial. The objective of this systematic review was to assess the safety and efficacy of low-intensity ultrasound therapy for MPS. Methods We searched PubMed, Embase, PEDro, Web of Science, and CENTRAL for RCTs on ultrasound therapy in MPS patients. We included RCTs comparing ultrasound with other therapies or placebo-sham ultrasound. Clinical outcomes included pain scores and physical functional performance. Risk of bias and heterogeneity were assessed. Two authors of the review independently evaluated the risk of bias of each trial and extracted the data. Results This systematic review included sixteen RCTs involving a total of 1063 participants with MPS. None of the included studies reported adverse events. Comparing with sham or no treatment, the application of low-intensity ultrasound yielded additional benefits for pain (SMD [CI] = − 1.04 [− 1.72, − 0.36], P < 0.0003), with high heterogeneity (χ2 = 116.63, P < 0.00001, I2 = 91%). Patients receiving low-intensity ultrasound had improved on pressure pain threshold. Compared with other treatments, there were no differences in outcomes functional scores. Conclusions The current study indicates that low-intensity ultrasound effectively reduces pain intensity in MPS patients. The heterogeneity regarding the parameters of ultrasound, including frequency, intensity, time was found to be high among the included studies. Each therapeutic modality works differently in various situations and may lead to multitudinous effects. The positive impact of low-intensity ultrasound on functional improvement needs to be further analyzed through more high-quality clinical trials with large sample sizes in the future. Trial registration This study was registered on the following website: https://www.crd.york.ac.uk/PROSPERO/ . The PROSPERO registered ID is CRD42023472032.